2018
DOI: 10.1149/2.0751809jes
|View full text |Cite
|
Sign up to set email alerts
|

Computer Study of Atomic Mechanisms of Intercalation/ Deintercalation of Li Ions in a Silicene Anode on an Ag (111) Substrate

Abstract: The ability of silicon to hold a large amount of lithium puts silicene in a series of the most promising materials for the anode of lithium-ion batteries. An increase in the rate of movement of lithium ions through silicene can be achieved with silicene having vacancy-type defects. The effect of vacancy-type defects on the fill ability with lithium of the channel formed by silicene sheets on the Ag (111) substrate, as well as on the structural and kinetic properties of lithium, has been studied by the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The remaining hg values were separated from each other by a distance of 0.1 nm. The lithium atoms in the channel with the gap hg = 0.75 nm could move quite freely along the channels located on the metal (Ag, Al, and Cu) substrates [5][6][7]35]. In the present work, the initial distance between the lower silicene sheet and the graphite substrate was 0.222 nm and corresponded to a similar value determined using the DFT calculations in Reference [36].…”
Section: Molecular Dynamic Simulation Techniquesupporting
confidence: 82%
See 3 more Smart Citations
“…The remaining hg values were separated from each other by a distance of 0.1 nm. The lithium atoms in the channel with the gap hg = 0.75 nm could move quite freely along the channels located on the metal (Ag, Al, and Cu) substrates [5][6][7]35]. In the present work, the initial distance between the lower silicene sheet and the graphite substrate was 0.222 nm and corresponded to a similar value determined using the DFT calculations in Reference [36].…”
Section: Molecular Dynamic Simulation Techniquesupporting
confidence: 82%
“…In References [5][6][7], it was shown that using the same procedure for lithium filling in an identical silicene channel that has no defects and is located on metal substrates (Ag, Al, Cu, and Ni) can achieve the presence of 39 to 74 Li atoms. The best channel occupancy with lithium (91 Li atoms) was achieved in the presence of monovacancies in the channel walls if the channel was placed on the Ni(111) substrate and in the presence of bivacancies (85 Li atoms) in silicene when the channel was on the Cu(111) substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a piece of silicene sheet of 336 Si atoms on the (111) surface of an Ag substrate with 2640 Ag atoms located in perfect fcc lattices (Figure 5a), the Tersoff potential was employed to describe the interactions between Si atoms with the parameters taken from [36], and the interaction between the Si atoms and the Ag atoms as described by a Morse pairwise function [52]. The system was cooled down to 0.01 K by a damping method [43,44] to determine the lowest energy U0 and the most stable structure.…”
Section: Demonstrations Of the Modelmentioning
confidence: 99%